Risk assessment and chemical fractionation of selected elements in surface sediments from Lake Qarun, Egypt using modified BCR technique. (January 2018) - Soliman, Naglaa F.; El Zokm, Gehan M.; Okbah, Mohamed A.
Abstract: In this study, spatial distribution and chemical fractionation were conducted to appraise the overall classification of Al, B, Cd, Cr, and Pb as well as their ecological risks in Lake Qarun sediments. Also, the other chemical components (CaCO3, TOC, SO4 2−, SiO3 2−, PO4 3−, F, Ca, and Mg) that represented the chemical composition of the sediments were determined. Modified BCR sequential extraction technique was used to evaluate the four (acid soluble, reducible, oxidizable and residual) fractions of the surface sediments. The association of Cd was found the highest with acid-soluble fraction (12.16–77.42%), while, Al (89.92–96.83%), B (42.32–93.93%), Cr (86.35–97.42%) and Pb (31.98–86.26%) were reside in residual phase. The degree of surface sediment contamination was computed by risk assessment code (RAC), individual contamination factor (ICF) and Global contamination factor (GCF). Risk assessment code classification showed that the relative amounts of easily dissolved phase of the investigated elements in the sediments are in the order of: Cd > Pb > B > Cr > Al. As a result, Cd had the highest risk to Lake Qarun. This study is a first approach of chemical fractionation of Al, B, Cd, Cr, and Pb in one of the most ecologically important Protectorates declared in the framework of Law 102 of year 1983. Information of this study constitutes a baseline of elements fractionation in Lake Qarun sediments and should be used as a reference for future studies on the changes of labile and residual elements fractions over time. Highlights: Distribution, fractionation and associated risk of Al, B, Cd, Cr and Pb in Lake Qarunsediments were investigated. The relative amounts of easily dissolved phase of the studied elements were in the order of Cd > Pb > B > Cr > Al. Potential ecological risk generally followed the pattern Cd > Pb > B > Cr > Al. Cd and Pb in Lake Qarun sediments were identified as the priority pollutants with high and moderate ecological risks.